Globalization, Democracy, and Social Movements: The educational potential of activism. Issue 10 (23rd August 2016) - Hytten, Kathy
Abstract: In this essay, I explore the contemporary value of John Dewey's conception of democracy to addressing the challenges of neoliberal globalization. I begin by describing his vision of democracy as a way of life that requires habits of experimentalism, pluralism, and hope. I then suggest that contemporary forms of mobilization, resistance, and insurgency—specifically, alter globalization activism, the Occupy Movement, and the Forward Together Moral Movement in North Carolina—model aspects of Deweyan democracy that are especially important for our times. These forms of civic activism can help reinvigorate Dewey's vision of democracy as rich, deep, participatory, and creative. I argue a significant value of these movements is the democratic habits and ways of life they encourage and support.